Impact dynamics in biped locomotion analysis: Two modelling and implementation approaches - Khalid Addi; Aleksandar D. Rodić (Mathematical Biosciences and Engineering)
Stability during the biped locomotion and especially humanoid robotswalking is a big challenge in robotics modelling. This papercompares the classical and novel methodologies of modelling andalgorithmic implementation of the impact/contact dynamics thatoccurs during a biped motion. Thus, after establishing the freebiped locomotion system model, a formulation using variationalinequalities theory via a Linear Complementarity Problem then animpedance model are explicitly developed. Results of the numericalsimulations are compared to the experimental measurements then theboth approaches are discussed.